Olfaction: Smell of Change in the Air - Doty, Richard L. (Cerebrum, 2017)
Every whiff you take not only brings a cloud of chemicals swirling up your nose, but matters to your experience of taste as well as smell. Scientists studying smell have not only provided compelling evidence that it’s more sophisticated than previously thought, but believe that the sense of smell impacts our mood and behavior and has the potential to detect and treat some neurological disorders. Compared to other senses, smell has long been underappreciated, writes our author, but that is now beginning to change.